Penerapan Togaf Adm Pada Arsitektur Sistem Informasi Absensi Dan Penggajian Di Desa Sri Purnomo - Tri Susilowati; Sucipto Sucipto; Widianto Widianto; Meliana Dewi (Prodi Sistem Informasi Universitas Dharma Andalas, 2023)
Building an information system in Sri Purnomo village requires IT governance from planning to implementation, so as to produce an organization that is able to achieve its goals optimally. Especially for village governments who want to run good-governance. Payroll operations and attendance attendance are currently done manually so that it slows down payroll calculations. Therefore it is necessary to collect data on the status of attendance, easy to find, and accessible to interested parties at any time, so that payment of salaries given to village officials is in accordance with applicable regulations. The Open This research focuses on the goal of designing an enterprise architecture in the form of a blueprint which includes business architecture, data architecture and application architecture to support Sri Purnomo Village information systems, especially attendance and payroll information systems. The Group Architecture Framework (TOGAF) offers a comprehensive method for managing, creating, and practicing existing business information architecture in the village. The use of Enterprise Architecture in the village of Sri Purnomo provides a clear picture of the system to be developed in the future and system integration.